Aggravated pneumonia and diabetes in SARS-CoV-2 infected diabetic mice - Qing Huang; Ran An; Haixuan Wang; Yun Yang; Cong Tang; Junbin Wang; Wenhai Yu; Yanan Zhou; Yongmei Zhang; Daoju Wu; Bai Li; Hao Yang; et al. (Emerging Microbes and Infections)
Multiple clinical and epidemiological studies have shown an interconnection between coronavirus disease 2019 (COVID-19) and diabetes, but experimental evidence is still lacking. Understanding the interplay between them is important because of the global health burden of COVID-19 and diabetes. We found that C57BL/6J mice were susceptible to the alpha strain of SARS-CoV-2. Moreover, diabetic C57BL/6J mice with leptin receptor gene deficiency (db/db mice) showed a higher viral load in the throat and lung and slower virus clearance in the throat after infection than C57BL/6J mice. Histological and multifactor analysis revealed more advanced pulmonary injury and serum inflammation in SARS-CoV-2 infected diabetic mice. Moreover, SARS-CoV-2 infected diabetic mice exhibited more severe insulin resistance and islet cell loss than uninfected diabetic mice. By RNA sequencing analysis, we found that diabetes may reduce the collagen level, suppress the immune response and aggravate inflammation in the lung after infection, which may account for the greater susceptibility of diabetic mice and their more severe lung damage after infection. In summary, we successfully established a SARS-CoV-2 infected diabetic mice model and demonstrated that diabetes and COVID-19 were risk factors for one another.